Persepsi Dan Partisipasi Masyarakat Muallaf Toraja Terhadap Upacara Adat Rambu Di Desa Gandangbatu, Kabupaten Tana Toraja - Meily Repture; Darman Manda (Universitas Negeri Makassar, 2023)
Abstract: This study aims to find out (1) How is the perception of the Toraja Muallaf community towards the Rambu Solo traditional ceremony. (2) What is the form of participation of the Toraja Muallaf community in the Rambu Solo traditional ceremony. (3) How is the social relationship that occurs between the Toraja Christian community and the Toraja Muallaf community in the Rambu Solo traditional ceremony in Gandangbatu Village/Lembang, Tana Toraja Regency. This research uses a type of qualitative research with a descriptive approach. Data collection techniques were obtained through several stages, namely observation, interviews and documentation involving several informants according to the required criteria. The results of this study indicate: (1) That the Muallaf Toraja community towards Rambu Solo' in Gandangbatu Village/Lembang has the perceptions of each individual, but all the perceptions expressed by them refer to positive perceptions. (2) The form of participation carried out by the Muallaf Toraja community in the Rambu Solo Ceremony in Gandangbatu Village/Lembang is realized by donating a material or non-material donation. (3) The social relations that occur between the Toraja Christian community and the Toraja Muallaf community have associative social relations and create a good, peaceful, peaceful and even harmonious atmosphere.